2011
DOI: 10.1007/s10669-011-9337-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 90Sr in milk and milk powder in Tehran and estimation of annual effective dose

Abstract: Thirty-eight different milk and milk powder samples from Tehran-Iran were collected and analyzed for 90 Sr activity using a method in which the daughter product of 90 Sr decay ( 90 Y) was extracted by tributyl phosphate from ashed milk. 90 Y was then back extracted with water, and oxalate was precipitated . Following the sample analyzing, beta counting was performed with an ultralow-level liquid scintillation spectrometer. The quality control and assurance of the method were obtained by standard samples prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In this study, the average value of 40 K in beef is lower than the values reported in Korea by Choi et al (2008), in Nigeria by Akinloye et al (1999) and in Italy by Meli et al (2013), while our obtained value is higher than the value reported by Harb et al (2010) in Egypt 14,28,30,31 . Similarly, 40 K concentrations in milk were higher than concentration in milk from other countries 13,14,28,32,33 . Table 5 reveals some differences in activity concentrations in animal products compared to the countries reported.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, the average value of 40 K in beef is lower than the values reported in Korea by Choi et al (2008), in Nigeria by Akinloye et al (1999) and in Italy by Meli et al (2013), while our obtained value is higher than the value reported by Harb et al (2010) in Egypt 14,28,30,31 . Similarly, 40 K concentrations in milk were higher than concentration in milk from other countries 13,14,28,32,33 . Table 5 reveals some differences in activity concentrations in animal products compared to the countries reported.…”
Section: Resultsmentioning
confidence: 85%
“…Natural radionuclides found in animal products consumed by humans such as beef, chicken, milk and eggs can be transferred to humans through food chain 12 . In a study in Iran conducted by Sarayegord et al (2009), the average activity concentrations for 40 K (31.0 ± 6.1 Bq.kg −1 ) in examined milk samples was used to calculate the effective dose of milk in adults as 14 µSv.year −1 13 . As a result of the study conducted in Egypt; the irradiation risk of human health was evaluated owing to indirect ingestion of the beef, milk, poultry and egg, the annual effective dose of the radionuclides for the local consumer was found to be as 2.7, 14.0, 0.1, and 0.14 µSv, respectively 14 .…”
mentioning
confidence: 99%